2019
DOI: 10.1017/s0021932019000324
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban differentials in fertility levels and fertility preferences in West Bengal, India: a district-level analysis

Abstract: Fertility in West Bengal is one of the lowest in India, and this relies heavily on the use of traditional methods of contraception. Social scientists and demographers have pointed to the historical role of the diffusion process of adhering to a small family size. The Total Fertility Rate (TFR) in Kolkata district, the state capital, is the lowest in the country, and has been a centre of low fertility historically. However, stark differences in rural–urban fertility rates have existed over the last few decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the present study, the third birth intention of the rural population was 1.203 times that of the urban population, which was consistent with the results from the 2012 Niger Demographic and Health Survey ( OR = 1.61, 95% CI = 1.20-2.17) [ 51 ]. Previous studies have also shown that the realization of fertility intention in rural areas is significantly higher than that in urban areas [ 52 , 53 ]. The reasons may be related to the different regional contexts and fertility ideologies [ 54 ], such as overall maternal employment, the high cost of living, and enhanced educational and labor market opportunities in the urban context.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the third birth intention of the rural population was 1.203 times that of the urban population, which was consistent with the results from the 2012 Niger Demographic and Health Survey ( OR = 1.61, 95% CI = 1.20-2.17) [ 51 ]. Previous studies have also shown that the realization of fertility intention in rural areas is significantly higher than that in urban areas [ 52 , 53 ]. The reasons may be related to the different regional contexts and fertility ideologies [ 54 ], such as overall maternal employment, the high cost of living, and enhanced educational and labor market opportunities in the urban context.…”
Section: Discussionmentioning
confidence: 99%
“…As the one-child policy had already been relaxed for rural residents since the 1980s, the increase in fertility is mainly based on urban women’s response to TCP. However, women in urban areas have higher education levels, which is a well-known factor of low-fertility intentions ( Chatterjee, 2020 ; Ghaznavi et al ., 2022 ). Additionally, a previous study indicated that people who were born in the only-child family were less willing to have more children ( Wang and Sun, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] It is important to note that though the acceptance and usage of contraception has been higher in West Bengal compared to the other Indian states 56 and that the use of modern family planning methods has increased substantially over the years in rural areas, the use of the natural method of family planning persists at a high rate in the rural areas of the state (13 percent). 57 In a recent study, Chatterjee (2019) found that, in West Bengal, the glaring differences in ruralurban fertility rates, observed in earlier decades, have started to converge recently. The study also found that the decline may be attributed to the fact that more than four out of ten women in rural areas have stopped childbearing before attaining the "desired" number of children.…”
Section: Work Which Have Led Up To the Studymentioning
confidence: 98%
“…2,3 Differences in the levels of fertility exist not only among states or between major and minor districts (in terms of development indicators) of a state but also between rural and urban areas. 4,5 The statistical reports of the Sample Registration System (SRS) of India reveal that TFR declined by nearly 28 percent between 1985-1986 and 2000-2001 and by 25 percent between 2001-2002 and 2015-2016. The decline was faster in urban areas compared to rural areas between 1985-1986 and 2000-2001 (30 percent in urban areas against an approximate 24 percent in rural areas); however, it was the other way round between 2001-2002 and 2015-2016 (18 percent in urban areas against about 27 percent in rural areas).…”
Section: Introductionmentioning
confidence: 99%